Firm self-financing, corruption, and the quality of tax administration in Africa - Toure Moumbark; Yawovi M. A. Koudalo (Cogent Economics & Finance, 2023)
This study aims to determine the impact of tax administration and corruption on firm self-financing in Africa. The paper also explores the level at which tax administration and corruption are firm financing obstacles and whether these effects on firms differ regarding their size. The article uses data from the World Bank Enterprise Survey, which covers 45,048 firms in 48 countries across Africa. Using the Tobit, IV Tobit, and Multinomial Probit models, the results are robust as we controlled for country, firm diversity, and survey year. The study reveals that corruption reduces a firm's self-financing by negatively affecting its internal funds or retained earnings. In addition, weak tax administration reduces firm self-financing. The results also reveal that corruption and poor tax administration are severe obstacles to a firm's self-financed. Furthermore, while weak tax administration generally harms firm financing, the negative impact on larger firms surpasses the adverse effects on smaller and medium firms. The corruption issue is more critical in the case of small and medium firms than big firms as they spend a large portion of their profit to government officials as gifts or informal payments to reduce the burden of regulations and circumvent taxes.
Keywords: D73; E62; H30; 330; Africa; Corruption; Firm self-financing; Tax administration